Rising commodity prices and welfare in Brazil. A short-run analysis using a SAM price model - Moncarz, Pedro Esteban (2017)
Fil: Moncarz, Pedro Esteban. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.